The Impact of Psychodynamic Theory-Based Resilience Training on Occupational Stress and Resilience Among Nurses - L Manalu, Fretty (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Hospitals offer extensive individualized medical care, while nurses perform specific tasks and fulfill distinct roles, which can cause significant stress among nurses. This study aimed to evaluate the effectiveness of psychodynamic resilience training in improving job stress management and endurance among nurses. Conducted in July 2023, the study involved 46 nurses at West Jakarta X Hospital. The research objectives were to assess the impact of psychodynamic resilience training on job stress levels and to determine the influence of such training on the resilience and endurance of nurses. The study employed a quantitative research approach with a quasi-experimental design, incorporating pre-and post-tests, control groups, and statistical techniques such as ANCOVA, t-tests, and multivariate analysis. The multivariate analysis demonstrated a substantial impact of PK and training on nursing work stress, with p-values of 0.008 and 0.000, respectively. Additionally, the resilience of nurses was significantly influenced by the implementation of resilience training, indicated by a p-value of 0.006, and the specific impact of resiliency training on nurse resilience showed a p-value of 0.020. The study found that psychodynamic resilience training effectively decreases work stress and enhances endurance among West Jakarta X Hospital nurses. Implementing psychodynamic theory is expected to enhance resilience training at X and Y hospitals, reducing work stress and increasing nursing resilience